2002
DOI: 10.1186/1471-244x-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of attention deficit/hyperactivity disorder among adults in obesity treatment

Abstract: Background: Bariatric patients showing poor "focus" during treatment more often failed to lose weight or maintain reduced weight. Evaluation of these patients identified a number having attention deficit/hyperactivity disorder (ADHD), evidently a potent factor limiting successful weight control. After searches found no published reports describing comorbid ADHD and obesity, this report was conceived to begin exploring the prevalence and characteristics of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
145
6
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(174 citation statements)
references
References 38 publications
11
145
6
10
Order By: Relevance
“…7 However, preliminary evidence surprisingly suggests a potential relationship between ADHD and obesity in clinical samples of obese adults and children seeking treatment. In a group of 215 adult patients treated for obesity, Altfas 8 found that 27.4% had ADHD (diagnosed according to DSM-IV criteria) and 33.5% presented with 'subthreshold' ADHD symptoms (i.e. symptoms of inattention and hyperactivity/impulsivity not meeting DSM-IV diagnostic criteria of ADHD).…”
Section: Introductionmentioning
confidence: 99%
“…7 However, preliminary evidence surprisingly suggests a potential relationship between ADHD and obesity in clinical samples of obese adults and children seeking treatment. In a group of 215 adult patients treated for obesity, Altfas 8 found that 27.4% had ADHD (diagnosed according to DSM-IV criteria) and 33.5% presented with 'subthreshold' ADHD symptoms (i.e. symptoms of inattention and hyperactivity/impulsivity not meeting DSM-IV diagnostic criteria of ADHD).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, when compared with normal weight individuals, obese subjects make less advantageous choices, which is a finding consistent with impaired inhibitory control and with prefrontal dysfunction (Pignatti et al, 2006). Moreover rates of attention deficit hyperactivity disorder (ADHD), which involves disruption in impulsivity, are elevated in obese individuals (Altfas, 2002). Similarly impulsivity has been linked with high BMI in some populations (Fassino et al, 2003) and in healthy controls BMI has also been associated with performance in tasks of executive function that mediate impulsivity (Gunstad et al, 2007).…”
Section: Study Limitationsmentioning
confidence: 84%
“…Type 2 DM is characterized by insulin resistance on target tissues such as the brain. Altfas (34) reported that ADHD was highly prevalent among obese patients and highest in those with extreme obesity. Bruehl et al (35) reported that adolescents with type 2 DM with insulin resistance have significantly reduced hippocampal and prefrontal volumes and higher rates of global cerebral atrophy as compared with obese controls without insulin resistance.…”
Section: Discussionmentioning
confidence: 99%